2014
DOI: 10.5751/es-06180-190126
|View full text |Cite
|
Sign up to set email alerts
|

Uneven Access and Underuse of Ecological Amenities in Urban Parks of the Río Piedras Watershed

Abstract: ABSTRACT. The association between consumption of ecological amenities in a park setting and improved physical and mental health substantiates the need for improved accessibility to green areas in lower-income neighborhoods. We measured green area accessibility, considering income variation, and park use in a densely populated tropical urban watershed. Park use was explored with 442 in-person interviews, and U.S. Census and Puerto Rico Commonwealth data were used to measure accessibility. Nearly 20% of resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…For land use planning in San Juan, our data products can serve to (1) identify patches of vegetation that can be converted to vegetable gardens, which is important for low income neighborhoods (Santiago et al. ), (2) improve precipitation runoff and flood models that require high‐resolution vegetation cover data, and (3) evaluate the status of riparian vegetation, which is important for maintaining water quality in the city.…”
Section: Discussionmentioning
confidence: 99%
“…For land use planning in San Juan, our data products can serve to (1) identify patches of vegetation that can be converted to vegetable gardens, which is important for low income neighborhoods (Santiago et al. ), (2) improve precipitation runoff and flood models that require high‐resolution vegetation cover data, and (3) evaluate the status of riparian vegetation, which is important for maintaining water quality in the city.…”
Section: Discussionmentioning
confidence: 99%
“…We know that the potential for trade-offs between GI services is an issue of concern in natural resource management as a factor that may detract from GI goals [70,71]. Perceptions of vegetation in public spaces as a dis-amenity (or dis-service) because of security and maintenance concerns has been shown to occur within RPWS [72]. Of significance here is the fact that those residents with more formal education also expressed greater likelihood to make changes in their yards.…”
Section: What Are the Drivers Of Yard Structure And Management In Sanmentioning
confidence: 96%
“…La Sierra, with the highest frequency of residents who do yard planting, hosts a coalition of neighborhoods that is engaged in the active planting of trees along the Arboretum of Cupey, an urban riparian forest that was incorporated into the San Juan Ecological Corridor, a protected urban forest under Law 206 of 2003 [79]. We also know from past work that these riparian corridors have had positive effects on housing prices within RPWS [72]. San Patricio and La Sierra showed lower frequencies of households with provisioning yard services (Figure 4).…”
Section: What Are the Drivers Of Yard Structure And Management In Sanmentioning
confidence: 99%
“…Ramos- Santiago et al (2014) studied three neighborhoods and found that those at a lower socioeconomic scale, i.e., Puerto Nuevo and Caparra Terrace, respectively lost at a minimum 60% and 55% of private green area and 85% and 79% of their public planting strip areas, whereas University Gardens with a higher socioeconomic level lost 36% of private green areas and 23% of public planting strip areas. All three communities had been planned communities that were subject to dramatic land cover changes as they aged, but one maintained more green infrastructure than the others, commensurate with socioeconomic level.…”
Section: Interaction Between People and Green Infrastructurementioning
confidence: 99%